1994
DOI: 10.2307/1939422
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Laxatives and Seed Passage Rates in Frugivores: Consequences for Plant Reproductive Success

Abstract: To explore how plants may influence dispersal of their own seeds by manipulating the behavior and physiology of their dispersers, we studied the effect of a soluble chemical (or chemicals) in the fruits of Witheringia solanacea (Solanaceae), a Costa Rican cloud forest shrub, on passage of its seeds through the guts of one of its major dispersers, the Black—faced Solitaire, Myadestes melanops (Muscicapidae: Turdinae). Using artificial fruits containing natural seeds, we found that the presence of a crude pulp e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
107
2
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(120 citation statements)
references
References 40 publications
(33 reference statements)
7
107
2
3
Order By: Relevance
“…Izhaki et al 1995). Seed germination success decreases as retention time increases (Murray et al 1994), which may explain low germination frequency of small consumed seeds (Traveset & Verdú 2002) in this study. Germination tests conducted in Petri dishes (used in this study) are also intermediate to detect differences between natural habitats and greenhouses.…”
Section: Plant Speciesmentioning
confidence: 67%
“…Izhaki et al 1995). Seed germination success decreases as retention time increases (Murray et al 1994), which may explain low germination frequency of small consumed seeds (Traveset & Verdú 2002) in this study. Germination tests conducted in Petri dishes (used in this study) are also intermediate to detect differences between natural habitats and greenhouses.…”
Section: Plant Speciesmentioning
confidence: 67%
“…How quickly and how thoroughly seeds are processed has important evolutionary consequences for both fruiting plants and frugivores (Herrera 1995;Murray et al 1994). Fruits are generally considered to be a food resource high in bulk (Herrera 1987), and bulk overloads the gut thereby reducing ingestion rate.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, various conflicts between fruiting plants and frugivorous birds, for example, fruit pulp production is costly for plants, but provides frugivores with energy (Sorensen 1984;Fukui 1996). Fruiting plants and frugivorous birds are also in conflict over seed retention time (SRT), which is defined here as: the time from ingesting a fruit to the time when its seed(s) are eliminated, corresponding to the time spent passing through the bird's digestive system.Several studies have suggested that seed dispersal distance is a function of SRT, however, small seeds tend to be dispersed further (Hoppes 1988;Murray et al 1994), indicating a relationship between seed size and SRT. Small seeds tend to remain in the gut longer than large seeds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, considering the relationship between seed size and disperser size (Casella & Cáceres 2006;Lessa & Costa 2010), it has been observed that smaller seeds remain trapped in the digestive system for a longer period of time than do larger seeds (Jordano 1992). A longer seed retention period reduces germinability (Murray 1994) or germination time, which may explain differences in germinability and germination time of very small seeds, such as C. urceolata (~ 1.0 mm) and P. crassifolium (~ 0.6 mm) eaten by larger species, such as D. albiventris. Therefore, the simple passage through the digestive tract of the disperser is not a prerequisite for increasing the germination of gut-passed seeds (Cantor et al 2010).…”
Section: Germinabilitymentioning
confidence: 99%